2022
DOI: 10.1093/bioinformatics/btab881
|View full text |Cite
|
Sign up to set email alerts
|

Current structure predictors are not learning the physics of protein folding

Abstract: Predicting the native state of a protein has long been considered a gateway problem for understanding protein folding. Recent advances in structural modelling driven by deep learning have achieved unprecedented success at predicting a protein’s crystal structure, but it is not clear if these models are learning the physics of how proteins dynamically fold into their equilibrium structure or are just accurate knowledge-based predictors of the final state. In this work, we compare the pathways generated by state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…At the 14th Critical Assessment of protein Structure Prediction (CASP), the AlphaFold 2 (AF2) system 12 outperformed all other computational methods, producing models rivaling experimental structures. 12 , 13 , 14 , 15 Although AlphaFold 2 has a limited applicability in modeling protein dynamics, multiple conformational states, or effects of mutations, 16 , 17 the approach is thought to achieve a significant progress in predicting the structure of a single protein chain. 12 Public availability of the AF2 source code and the recent release of the AlphaFold DataBase 18 with over half a million protein models, including the full proteomes of 16 model organisms and 32 pathogens, are starting to have a transformative impact on structural biology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the 14th Critical Assessment of protein Structure Prediction (CASP), the AlphaFold 2 (AF2) system 12 outperformed all other computational methods, producing models rivaling experimental structures. 12 , 13 , 14 , 15 Although AlphaFold 2 has a limited applicability in modeling protein dynamics, multiple conformational states, or effects of mutations, 16 , 17 the approach is thought to achieve a significant progress in predicting the structure of a single protein chain. 12 Public availability of the AF2 source code and the recent release of the AlphaFold DataBase 18 with over half a million protein models, including the full proteomes of 16 model organisms and 32 pathogens, are starting to have a transformative impact on structural biology.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Public availability of the AF2 source code and the recent release of the AlphaFold DataBase 18 with over half a million protein models, including the full proteomes of 16 model organisms and 32 pathogens, are starting to have a transformative impact on structural biology. 13 , 15 , 16 Despite the varying quality of AF2‐generated models, they have been added to high‐quality authoritative resources for protein sequences, structures, and functional information, such as UniProt 4 and PDBsum. 19 The availability of high‐accuracy predictions for a significant portion of many organisms' proteomes is a novel source of information into bitopic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable, however, that AlphaFold2’s predictions miss the ground state of fold switchers 30% of the time. This is further evidence that its predictions are primarily rooted in sophisticated pattern recognition, not protein biophysics 37 .…”
Section: Discussionmentioning
confidence: 75%
“…and kinetics (what pathways do proteins traverse between unfolded and folded states?) 4; 36 , deep learning approaches reveal apparent properties of experimentally determined protein structure rather than biophysical pathways 37 . Thus, it is not surprising that its predictions often fail for proteins whose properties are not fully apparent from solved protein structures, such as IDPs 5-7 .…”
Section: Discussionmentioning
confidence: 99%
“…14 This approach has not provided much information on the molecular level details of a protein model. While AlphaFold 2 does not elucidate the physical manner in which a protein folds, 15 it has been shown to predict protein backbones with high accuracy when compared to experimental structures, however, less attention has been paid to side-chain structure in AlphaFold 2 models. A recent paper reported that for the three CASP14 proteins that had bound ligands of S-adenosylmethionine or adenosine-5'-diphosphate in their experimental structures, the homology model had the same location of binding but the binding pose was different than the experimental structure.…”
Section: Introductionmentioning
confidence: 99%